2013
DOI: 10.1089/apc.2012.0269
|View full text |Cite
|
Sign up to set email alerts
|

Health Care and HIV Testing Experiences Among Black Men in the South: Implications for “Seek, Test, Treat, and Retain” HIV Prevention Strategies

Abstract: Few studies have explored how overall general health care and HIV/STI testing experiences may influence receipt of "Seek, Test, Treat, and Retain" (STTR) HIV prevention approaches among Black men in the southern United States. Using in-depth qualitative interviews with 78 HIV-negative/unknown Black men in Georgia, we explored factors influencing their general health care and HIV/STI testing experiences. The Andersen behavioral model of health care utilization (Andersen model) offers a useful framework through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…Correctional facilities have been identified as important venues for reaching persons at risk for HIV, particularly for racial and ethnic minorities who face disparate rates of incarceration compared to nonminorities. 25 However, our findings reinforce other studies that have revealed the challenges of delivering HIV treatment and high quality HIV care to persons who cycle in and out of the criminal justice system. 26 This study demonstrates that new HIV diagnoses can be identified through routine opt-out testing in jail and those persons who remain incarcerated for at least 2 weeks can be considered for initiation of ART.…”
Section: Discussionsupporting
confidence: 87%
“…Correctional facilities have been identified as important venues for reaching persons at risk for HIV, particularly for racial and ethnic minorities who face disparate rates of incarceration compared to nonminorities. 25 However, our findings reinforce other studies that have revealed the challenges of delivering HIV treatment and high quality HIV care to persons who cycle in and out of the criminal justice system. 26 This study demonstrates that new HIV diagnoses can be identified through routine opt-out testing in jail and those persons who remain incarcerated for at least 2 weeks can be considered for initiation of ART.…”
Section: Discussionsupporting
confidence: 87%
“…Isolating STI services and messages that produce negative and discriminatory perceptions may only contribute to STI stigma and shame. Integrated services 12 have been recommended, especially for people of color who experience major health disparities and barriers to accessing services 35,36 and for attracting and retaining young clients, especially by virtue of offering convenience and ''camouflaging'' services that carry stigma. 37 Integrated services in this context may lead to raised awareness, increased uptake and frequency of testing, less delay in care seeking, and greater uptake and success of partner notification and treatment programs.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that provide direction on PrEP uptake have been defined and are well-articulated, 38,[40][41][42][43] however, public health agencies and primary care providers need to develop stronger ties in order to identify and link to ongoing care individuals who are at elevated risk for HIV. Although historically much of the HIV prevention and treatment efforts in the US have been carried out by community-based HIV/ AIDS organizations, many of these agencies are likely unequipped within their currently existing infrastructure to not only raise awareness of PrEP, but seek out, engage, and provide ongoing care for individuals who are on PrEP or candidates for PrEP.…”
Section: Prep Awareness Among Bmsm 427mentioning
confidence: 99%